Utilization of The Museum of Kekhatuan Semaka as A Source Of Learning In Local History - Andre Mustofa Meihan; Sariyatun Sariyatun; Deny Tri Ardianto (Universitas Sebelas Maret, 2020)
The purpose of this study was to determine: 1) Management and types of collections at the Kekhatuan Semaka Museum; 2) Utilization of the kekhatuan semaka museum collection as a source of historical learning; 3) The Museum's strategy for self-promotion. The research method used is descriptive qualitative. The data collection techniques used were literature study, interview, observation, and documentation. The object of research is Kekhatuan semaka Museum. The data analysis technique used is interaction analysis, with four stages, namely data collection, data reduction, data presentation, and drawing conclusions or verification. Based on the results of the discussion, it can be concluded that: 1) The management of the kekhatuan semaka museum is carried out independently by the museum owner and the museum collection includes historical heritage objects and objects of Lampung culture; 2) The use of the Khatuan semaka Museum Collection as a source of historical learning is by linking it with KD and history learning materials; 3) The form of promotion carried out by the kekhatuan semaka museum through social media and annual festivals.